PELATIHAN DIGITAL MARKETING KEPADA PENGRAJIN PEMBUAT SABUN CUCI PIRING DESA TINAWUN MALO BOJONEGORO : (Digital Marketing Training for Dishwashing Soap Manufacturers in Tinawun Village Malo Bojonegoro) - Zumrotus Sa’diyah; M. Romadlon Habibullah; Nurul Mahruzah Yulia (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2022)
In general, Tinawun Village has a lot of potential to become a prosperous and prosperous village. In addition to having fertile soil, good human resources, healthy and conducive village government, Tinawun Village has one potential village tourism, namely Religious tourism to the Tomb of Sheikh Zakaria every Kliwon Friday. However, apart from tourism, there are many things that can be used in Tinawun Village, namely corn, which is usually only used for cooking, but now it can be used as a source of income for residents by making rice. In addition to corn, there is also ginger which is usually only used as an additional spice in the kitchen, now it can be processed into a drink that is rich in benefits and helps increase body immunity, by mixing it with various flavors, it can be turned into an immune boosting drink that can increase the body's immunity during this pandemic. Apart from the plant aspect, there is also the empowerment of catfish as an income source for local residents.